2005
DOI: 10.1007/s10479-005-2451-4
|View full text |Cite
|
Sign up to set email alerts
|

Scatter Search for Network Design Problem

Abstract: A fixed charge capacitated multicommodity network design problem on undirected networks is addressed. At the present time, there exists no algorithm that can solve large instances, common in several applications, in a reasonable period of time. This paper presents an efficient procedure using a scatter search framework. Computational experiments on a large set of randomly generated problems show that this procedure is capable of finding good solutions to large-scale problems within a reasonable amount of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…When updating the pool of solutions, the dissimilarity of solutions is considered as an additional component in calculating the solution value. Alvarez et al (2005) describe an SS algorithm for the MCNDP. They use GRASP, originally proposed by Feo and Resende (1995), to produce a diversified initial set of solutions.…”
Section: Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…When updating the pool of solutions, the dissimilarity of solutions is considered as an additional component in calculating the solution value. Alvarez et al (2005) describe an SS algorithm for the MCNDP. They use GRASP, originally proposed by Feo and Resende (1995), to produce a diversified initial set of solutions.…”
Section: Literaturementioning
confidence: 99%
“…A feasibility restoration mechanism is also available for solutions that are infeasible. In contrast to the recombination process of Alvarez et al (2005), our SS does not consider commodity paths to build a solution; instead, independent arcs are combined to create offspring. We believe that the latter enhances the SS algorithm's capabilities, as more combinations can occur when arcs instead of paths are combined together, leading to a rich pool of offspring.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…They showed that the designed population-based algorithms provide better results compared to other methods. Later, Alvarez et al (2005) proposed a scatter search approach for solving a general network design problem for undirected networks. They showed that this algorithm is capable for finding good solutions in large-scale problems within a reasonable time.…”
Section: First Step Of the Algorithmmentioning
confidence: 99%